Purifikasi dan karakterisasi parvalbumin patin dan gurami: Purification and characterization of catfish and gourami parvalbumin - Nugraha, Roni; Safitri, Novemi Gita; Nurilmala, Mala; Pertiwi, Rizsa Mustika (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Parvalbumin is the main protein responsible for fish allergies. However, allergic sufferers show different reactions to different types of fish. Therefore, it is important to purify and character-ize parvalbumin from various fish species. In this study, parvalbumin from raw and cooked catfish and gourami fish was purified and characterized. Parvalbumin was purified using the ammonium sulfate precipitation method and identified using SDS-PAGE. The allergenic properties of parvalbumin from gourami and catfish were analyzed in silico. Protein profiling using SDS-PAGE showed the presence of two bands representing parvalbumin with molecu-lar weights ranging from 12-14 to kDa. Purification using ammonium sulfate did not result in pure parvalbumin because the other protein bands were still quite thick. However, ammonium sulfate at 80-90% saturation produced the best profile in the purification process of parvalbu-min from raw fish and 90-10% for cooked fish. Bioinformatics analysis showed seven parval-bumin sequences in catfish, but no parvalbumin sequences were found in gourami fish. One catfish parvalbumin sequence with the code XP_026772003.1, showed high similarity with parvalbumin from other species known to be allergenic. The results of this study can serve as a basis for further characterization of parvalbumin to support better diagnosis.